Isolation with differentiation followed by expansion with admixture in the tunicate Pyura chilensis - Haye, Pilar A; Muñoz-Herrera, Natalia C (BMC evolutionary biology, 2013)
Background Pyura chilensis , a tunicate commercially exploited as food resource in Chile, is subject to management strategies, including restocking. The goal of this study was to examine the genetic structure of P. chilensis using information from a mitochondrial gene (Cytochrome Oxidase I, COI) and a nuclear gene (Elongation 1 alpha, EF1a) , to characterize the geographic distribution of genetic diversity and differentiation, and to identify the main processes that have shaped it. We analyzed 268 and 208 sequences of COI and EF1a, respectively, from samples of eight local populations covering ca. 1800 km. Results For Pyura chilensis , partial sequences of the gene COI revealed three highly supported haplogroups that diverged 260000 to 470000 years ago. Two haplogroups currently are widely distributed and sympatric, while one is dominant only in Los Molinos (LM, 39°50′S). The two widespread COI haplogroups underwent a geographic expansion during an interglacial period of the Late Pleistocene ca. 100000 years ago. The nuclear gene was less divergent and did not resolve the COI haplogroups. Bayesian clustering of the nuclear gene’s SNPs revealed that individuals from the two widespread COI haplogroups were mostly assigned to two of the three detected clusters and had a marked degree of admixture. The third cluster predominated in LM and showed low admixture. Haplotypic diversity of both genes was very high, there was no isolation by distance, and most localities were genetically undifferentiated; only LM was consistently differentiated with both genes analyzed. Conclusions Pyura chilensis has less genetic structure than expected given its life history, which could be a consequence of dispersal on ship hulls. The only differentiated local population analyzed was LM. Coincidentally, it is the one furthest away from main maritime routes along the coast of Chile. The use of mitochondrial and nuclear markers allowed detection of divergent mitochondrial haplogroups in P. chilensis , two of which revealed nuclear admixture. The genetic structure of P. chilensis has likely been shaped by Pleistocene’s climatic effect on sea level leading to population contraction with isolation, followed by geographic range expansions with concomitant secondary contact and admixture.